Quality Evaluation of Ideological and Political Education in Universities Based on BP Neural Network. (18th July 2022) - Ding, Yunxia; Zeng, Wei; Ning, Zhen
Abstract : At present, there are some problems in the research of curriculum ideological and political quality evaluation, such as insufficient theme attention, insufficient theoretical research, incomplete data collection, and so on. This study aims to use the BP neural network in the ideological and political quality evaluation system so that the system can more comprehensively and accurately reflect the actual situation of students and point out the direction for the development of students' ideological and political education. The construction of this system can provide a very considerable and accurate way for the quality evaluation of ideological and political education of college students and especially solves the problems of human subjective, factor errors, and the setting of evaluation index weights in the evaluation system.